(untitled) (Journal of Engineering, 2012)
Reconstruction in Iraq requires coherent legitimate frameworks that are able to detail obligations, rights and responsibilities of the parties participating in reconstruction projects, regardless their type or delivery system. Conditions of Contract can be considered an important component of these frameworks. This paper investigates flexibility and appropriateness of the application of Iraqi conditions of contract in reconstruction projects. These conditions were compared to FIDIC Conditions. The objective wasn’t comparing individual clauses, but rather exploring the principles and philosophy laying behind each conditions, and to what extent each conditions care about realizing equity between main contract parties. Validity of application on various project delivery systems was also investigated. The structure of Iraqi and FIDIC conditions were compared to determine how the efficiency of use will be effected by the layout, presentation, organization, and detailing of the contents of each conditions. Moreover, some clauses related to the project parties were compared in order to further illustrate the disparity in efficiency of each conditions. The paper concludes that Iraqi conditions of contract in its current state was, and will continue, hindering the reconstruction efforts in Iraq, as well as being a cause of money waste and bad quality of project outputs.